Intracontinental and intercontinental dissemination of Asian H5 highly pathogenic avian influenza virus (clade 2.3.4.4) in the winter of 2014–2015. (13th October 2015) - Saito, Takehiko; Tanikawa, Taichiro; Uchida, Yuko; Takemae, Nobuhiro; Kanehira, Katsushi; Tsunekuni, Ryota
Summary: Asian H5 highly pathogenic avian influenza viruses (HPAIVs) that possess the clade 2.3.4.4 HA gene have been identified in wild birds and poultry since late 2014 in both Europe and North America (N. America). Clade 2.3.4.4 H5 HPAIVs of the H5N8 subtype have been isolated in both regions, whereas reassortment viruses with NA N1 and N2 subtypes of the North American (N. American). avian lineage have only been identified in N. America. The HA genes of those isolates were closely related to genes of the HPAIVs that have caused massive outbreaks in poultry in Korea since January 2014. The outbreaks caused by those viruses and the genetic relatedness of their HA and NA genes are reviewed in this study. Although the illegal movement of poultry and poultry products cannot be ruled out as a cause of intercontinental and intracontinental dissemination of clade 2.3.4.4 H5 HPAIVs during the winter of 2014–2015, transmission of the viruses by infected migratory birds appears to be a more plausible mechanism for their dissemination. In particular, the involvement of migratory birds in HPAIV transmission between Asia and N. America is highly likely because of the reassortments between H5N8 HPAIV and the N. American lineage avian influenza viruses. Copyright © 2015 John Wiley & Sons, Ltd.